PROJECT MANAGEMENT OF ENTERPRISE INNOVATIVE POTENTIAL AND DEVELOPMENT - Zanora, Volodymyr (Zhytomyr Ivan Franko State University, 2019)
It is noted that under unfavorable conditions of economic activity, which characterizes the economic climate of Ukraine, an important aspect of the enterprises effective functioning is the effective management of innovation potential and development. The definition of the category «innovative potential» is considered and two main approaches to interpreting the term are given, namely resource and productive. It is established that innovative potential and development are considered today both in relation to the enterprise innovative activity and in relation to its economic activity in general. The expediency of using the project approach on the management of innovative potential and development of the enterprise with regard to the proven practice of using the project management methodology in the context of the functioning of the enterprise is stated. The simplified structural and logical scheme of project management of innovation potential and development is presented. The need for multi-project management of the enterprise potential and development was emphasized. A portfolio of projects in the context of enterprise potential  management and development management has been formed.